Analisa Risiko Pajanan Okupasional Partikulat Dalam Ruang Bahan Bangunan - Deddy Alif Utama; Fitriani Sudirman; Syakila Gita Diandra (Buletin Keslingmas, 2026)
Loading and unloading activities in building material stores generate suspended coarse particulate matter (PM10) emissions, risking respiratory disorders among workers due to inadequate ventilation. This study aimed to evaluate PM10 concentrations, estimate environmental health risk levels (Risk Quotient/RQ), and quantitatively analyze their relationship with the severity of workers' respiratory complaints in Gorontalo City. This cross-sectional observational analytic study utilized an Environmental Health Risk Assessment (EHRA) approach involving 15 workers via total sampling. PM10 concentrations were measured using a Portable Dust Monitor across three work zones: Cement Warehouse, Display Area, and Mixed Material Warehouse. Bivariate data analysis applied Fisher's Exact Test and Spearman Rank correlation. The results demonstrated an extreme concentration disparity where the Cement Warehouse (177.79 µg/m³) significantly exceeded the daily threshold limit of 70 µg/m³ due to a pollutant trap effect, far surpassing the Display Area (11.43 µg/m³) and Mixed Warehouse (11.61 µg/m³). Respiratory complaint prevalence was remarkably high at 93.3% (dominated by sneezing at 60%). Fisher's Exact Test showed no categorical association between risk status and complaint occurrence (p=1.000) due to high baseline prevalence across all zones. However, the Spearman Rank test proved a strong and statistically significant positive correlation between direct PM10 concentrations and respiratory complaint severity (r=0.640; p=0.010). In conclusion, particulate matter triggers mass initial mucosal irritation, but the clinical severity of respiratory disorders is strictly dose-dependent on concentration levels. The high severity of complaints in pollutant trap areas strictly demands engineering controls, specifically Local Exhaust Ventilation (LEV), to suppress PM10 concentrations and prevent respiratory deterioration.